HEGEMONI PARTAI POLITIK TERHADAP KINERJA ANGGOTA DEWAN PEREMPUAN DI DPRD PROVINSI JAWA TENGAH PERIODE 2019-2024 - Febriyani Puspita Pratiwi; Puji - Astuti (Journal of Politic and Government Studies, 2020)
The existence of women in legislative institutions is an absolute form of participation in the democratic process of the Indonesian nation. From this meaning, it is hoped that their existence will be able to give birth to policy sensitivity oriented to the interests of women. In fact women often encounter some obstacles in politics, such as political party rules that suppress women's independence and the dominance of the number of men who occupy seats in the council. The purpose of this study was to determine The Political Parties Hegemony Toward the Performance of Women Council Members In DPRD Province of Central Java 2019-2024 Period amidst of the existence of double hegemony originating from political parties and male domination in this representative institution. This research used descriptive analytical method with a qualitative approach. Data collection techniques used were interviews, and data collection techniques were also carried out with literature review and document review. Based on the results of the study, the researcher found that the women played active role when they expressed their opinions in running out the legislative function. However, with the collegial collective system made the women did not able to optimally convey the draft local regulation independently. In carrying out the budget function, women played an active role in the planning processed, discussion, stipulation, monitoring and evaluation processed in the determination of the APBD. There were some activities to carry out the oversight function such as the role of women councillor was quite active by carrying out recess, The women councillor did a work visits with OPD partners and based on OPD partners the role of board members was quite active in voicing the needs of their constituents. In the conclusion, despite the women councillor was under the shadow of the hegemony of political parties as a place for them to take shelter and the dominance of men in terms of quantitative, members of the council prove that they are able to greet opinions and try to play an active role as a member of the board in order to prosper the people of Central Java